Pengaturan Penggunaan Tenaga Kerja Asing di Kawasan Ekonomi Khusus - Yuli Andini Puspitasari; Navyra Berlianny; Mila Sari; Putri Yanti; Muhammad Fajar Hidayat (Pusat Riset dan Inovasi Nasional, 2024)
Special Economic Zones in Indonesia are zones that are provided with special facilities to increase investment and national competitiveness. Special economic zones consist of several zones, including export processing zones, logistics zones, industrial zones, technology development zones, energy zones and other economic zones. The use of foreign workers in special economic zones has limitations and potential, which need to be understood so that the benefits can be maximized. These limitations include regulations and compliance, regulatory compliance, and local energy absorption. Meanwhile, the potential for using foreign workers in special economic zones includes technology and skills, easier access to foreign workers, regional economic development, and increasing company productivity.